Audiovisual Speech Synchrony Measure: Application to Biometrics. (7th May 2007) - Bredin Bredin, Hervé Hervé; Chollet Chollet, Gérard Gérard
Abstract : Speech is a means of communication which is intrinsically bimodal: the audio signal originates from the dynamics of the articulators. This paper reviews recent works in the field of audiovisual speech, and more specifically techniques developed to measure the level of correspondence between audio and visual speech. It overviews the most common audio and visual speech front-end processing, transformations performed on audio, visual, or joint audiovisual feature spaces, and the actual measure of correspondence between audio and visual speech. Finally, the use of synchrony measure for biometric identity verification based on talking faces is experimented on the BANCA database.